2020
DOI: 10.3390/ijerph17207633
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Evaluation and Optimization of Community Epidemic Prevention in Wuhan Based on a DEA Model

Abstract: Background—Communities played a key role in preventing the spread of coronavirus, not only during the threshold period of the epidemic but also in the normal stage of prevention. Scientifically evaluating the community’s work is necessary for prevention in the normal period of the epidemic and can provide a reference for the management of different countries. Methods—Based on data envelopment analysis (DEA), this article used community worker data to evaluate the matching of service supply and demand during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The severity of Covid-19 and management measures of government have substantial impact on public, which is necessary to response timely by multiple ways to various problem and needs of public. The differences of pandemic severity in different regions and problems arising from lockdown management, such as mental problem [ 48 ], will prompt community to have multiple roles in taking measures and providing services [ 63 ]. When facing limited health resources in crisis management, to achieve a balance between ethical issues and clinical management, pandemic prevention measures must be taken [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of Covid-19 and management measures of government have substantial impact on public, which is necessary to response timely by multiple ways to various problem and needs of public. The differences of pandemic severity in different regions and problems arising from lockdown management, such as mental problem [ 48 ], will prompt community to have multiple roles in taking measures and providing services [ 63 ]. When facing limited health resources in crisis management, to achieve a balance between ethical issues and clinical management, pandemic prevention measures must be taken [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that influenza and other acute respiratory infections, and now also COVID-19, are the most widespread diseases that occur throughout the year, but most often in autumn and winter. According to the World Health Organization, SARS ranks first in the structure of infectious diseases and accounts for 80-90% of all infectious pathology [12]. The economic damage from the recent COVID-19 pandemic is huge, and it is a loss both for an individual (lost working days, medicine costs) and for society as a whole [13].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mackworth-Young [14] conducted telephone interviews and found that in pandemic prevention and control, personal protective equipment and sufficient salaries for health care workers, as well as provisions to meet residents' basic needs, are prerequisites for communities to take effective preventive measures. In a report by Zhang Yuxiao [15], it is recommended that, when a public health emergency occurs, the government should take measures to improve the quality of residents' lives and coordinate prevention and control efforts, including dispatching enough service personnel, mobilizing service resources, refining service content, and adjusting incentive policies so as to effectively prevent and control the spread of the pandemic and further expedite the economic and social recovery. The management and deployment of public resources in a community are often key to preventing and controlling outbreaks during a pandemic.…”
Section: Introductionmentioning
confidence: 99%